PREPARATION AND CHARACTERIZATION OF TiO2-ZEOLITE AND ITS APPLICATION TO DEGRADE TEXTILLE WASTEWATER BY PHOTOCATALYTIC METHOD - Yeslia Utubira; Karna Wijaya; Triyono Triyono; Eko Sugiharto (Universitas Gadjah Mada, 2006)
The preparation of titanium oxide-zeolite composite (TiO2-zeolite) has been done. Preparation was initiated by dispersing oligocation of titanium solution into suspension of natural zeolite. The suspension was stirred and then filtered to separate the solid phase from the filtrate. The solid phase was heated by microwave oven to convert the oligocations into its oxide forms and the resulting material (called as TiO2-zeolite) then was used to photodegrade the wastewater of PT.Jogjatex The TiO2-zeolite and unmodified zeolite were characterized using X-ray diffractometry, FT-IR spectro-photometry, X-ray fluorescence (XRF) and gas sorption analysis (GSA) methods to determine their physicochemical properties. Photocatalytic activity of TiO2-Zeolite was tested by exposing the suspension of TiO2-Zeolite/wastewater by the UV light of 366 nm at room temperature for 15 - 75 minutes. Characterization results exhibited that the formation of TiO2 on internal as well as external surfaces of Zeolite could not be detected with X-ray diffractometry as well as FT-IR spectrophotometry, however elemental analysis result with XRF indicated that titanium concentration in zeolite increased due to the inclusion, i.e from 0.26% (w/w) in zeolite to 2.80% (w/w) in TiO2-zeolite. Characterization result by GSA exhibited the increased of specific surface area from 19.57 m2/g in zeolite to 67.96 m2/g in TiO2-zeolite; total pore volume from 20.64 x 10-3 mL/g in zeolite to 49.561 x 10-3 mL/g in TiO2-Zeolite; pore radius average decreased from 21.10 Å in zeolite to 14.58 Å in TiO2-zeolite. Photocatalytic activity test of TiO2-zeolite on wastewater of PT. Jogjatex showed that UV radiation for 75 minutes on the mixture of TiO2-zeolite and wastewater resulted in the decreased of COD number up to 57.85%. Meanwhile the sorption study showed that zeolite and TiO2-zeolite could decrease COD number of wastewater up to 43.95% and 57.85%, respectively.